A Systematic Review and Meta-Analysis of Burnout Among Healthcare Workers During COVID-19 - Ghahramani, Sulmaz; Lankarani, Kamran Bagheri; Yousefi, Mohammad; Heydari, Keyvan; Shahabi, Saeed; Azmand, Sajjad (Frontiers in Psychiatry, 2021)
Burnout among healthcare personnel has been exacerbated by the COVID-19 pandemic's unique features. During the COVID -19 pandemic, this systematic review and meta-analysis aims to provide a complete assessment of the prevalence of burnout across various healthcare personnel. Until January 2021, systematic searches for English language papers were conducted using PubMed, Scopus, EMBASE, Web of Science, Cochrane Library, and ProQuest. 30 observational studies were found after conducting systematic searches. The pooled overall prevalence of burnout was 52% (95% Confidence Interval (CI) 40-63%). Pooled emotional exhaustion (EE), depersonalization (DP) and lack of personal accomplishment (PA) were 51% (95% CI 42- 61%), 52% (95% CI 39- 65%), and 28% (95% CI 25- 31%) ,respectively. This study demonstrated that nearly half of the healthcare workers experienced burnout during the COVID-19 pandemic. In the studies that were included, non-frontline COVID-19 exposed healthcare personnel also experienced burnout. From high to lower middle-income countries, there was a gradient in the prevalence of total burnout, EE, and lack of PA. Further studies on burnout in low and lower-middle-income countries are suggested. A uniform diagnostic tool for the assessment of burnout is warranted.